Про симетрію комбінаторних множин - Тимофієва, Н.К. (Управляющие системы и машины, 2017)
Исследована симметрия в комбинаторике, в частности свойственная упорядоченным по определенным правилам комбинаторным множествам. Ее математическая формулировка проводится с использованием конечных последовательностей, которые характеризуются приближенной или точной симметрией. Приведены примеры построенных последовательностей для комбинаторных множеств, которые упорядочиваются подмножествами изоморфных комбинаторных конфигураций. Показано, что для задачи коммивояжера распределение тождественных маршрутов в их множестве симметрично. Досліджено симетрію в комбінаториці, зокрема властиву упорядкованим за певними правилами комбінаторним множинам. Її математичне формулювання проводиться з використанням скінченних послідовностей, які характеризуються наближеною або точною симетрією. Подано приклади побудованих послідовностей для комбінаторних множин, які упорядковуються підмножинами ізоморфних комбінаторних конфігурацій. Показано, що для задачі комівояжера розподілення тотожних маршрутів у їхній множині – симетричне. In the article the symmetry of the combinatorial set of configurations is ordered by the certain rules. We don’t focus on the release of symmetric groups and the identification number of their species. We has studied some properties of the symmetric sets. For combinatorial sets of different types of combinatorial configurations the finite sequence is built, which is defined as the approximate and exact symmetry. For combination without repetition for different values n of these sequences the arithmetical triangle is formed and it is characterized by exact symmetry. For integer partitioning or partitioning n -element set into subsets the finite sequence is created, it is characterized by the approximate symmetry. For the traveling salesman problem the number of identical and different routes are defined. It is shown that in their set they are distributed symmetrically. The results can be used in solving the combinatorial optimization problems of different classes to analyze changes in the values of the objective function depending on the structure of input data sets based on the combinatorial